An overview of heterojunctioned ZnFe2O4 photocatalyst for enhanced oxidative water purification. Issue 5 (October 2021) - Sonu,; Sharma, Sheetal; Dutta, Vishal; Raizada, Pankaj; Hosseini-Bandegharaei, Ahmad; Thakur, Vijay; Nguyen, Van-Huy; VanLe, Quyet; Singh, Pardeep
Abstract: A number of studies on zinc ferrite (ZnFe2 O4 ) as photocatalyst in cleaning wastewater have been achieved, because zinc ferrite nanoparticles are less toxic, chemically stable, possess high magnetic crystalline anisotropy, high coercivity, good magnetization, are biocompatible and cost-effective. Besides, separation of zinc ferrite photocatalyst is facile due to its magnificent magnetic behavior. The current review addresses zinc ferrite as a promising photocatalyst, its magnetic properties and electronic structure. Furthermore, various synthesis techniques have been reviewed viz. hydrothermal, sol-gel, polyol, co-precipitation, microwave, solvothermal, microemulsion, etc. for zinc ferrite photocatalysts. Various strategies for enhancing photocatalytic performances of heterojunctioned zinc ferrite photocatalysts were thoroughly reviewed. In conclusion, challenges and upcoming research requirements in edict to improve photocatalytic applications of zinc ferrite photocatalysts are addressed. Graphical Abstract: ga1 Highlights: An outline on ZnFe2 O4 based photocatalysts is presented. The structure and magnetic properties of ZnFe2 O4 based photocatalysts are discussed. Photocatalytic applications are explored comprehensively. Future outlook on ZnFe2 O4 based photocatalysts is reviewed.